1993
DOI: 10.1002/ana.410330304
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni strains from patients with guillain‐barré syndrome belong mostly to penner serogrpup 19 and contain β‐N‐acetylglucosamine residues

Abstract: Campylobacter jejuni was isolated from stool cultures from 14 (30%) of 46 patients with Guillain-Barré syndrome and from 6 (1.2%) of 503 healthy persons, and the difference was highly significant (p < 0.0001). In addition, serological evidence of recent C. jejuni infection was found in 5 of 29 patients with negative stool cultures. Therefore, 41% of patients were associated with C. jejuni infection. Ten of 12 (83%) isolates from patients with Guillain-Barré syndrome belonged to Penner serogroup 19, which is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
2
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(54 citation statements)
references
References 20 publications
(7 reference statements)
1
49
2
2
Order By: Relevance
“…Thus, few surveillance studies have included large numbers of patients. Kuroki et al (17) reported that 30% of 46 GBS patients in the Kinki district of Japan had positive stool cultures. In a subsequent study, these authors isolated 13 strains (17%) of C. jejuni from 76 patients (9).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, few surveillance studies have included large numbers of patients. Kuroki et al (17) reported that 30% of 46 GBS patients in the Kinki district of Japan had positive stool cultures. In a subsequent study, these authors isolated 13 strains (17%) of C. jejuni from 76 patients (9).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple stool samples (or rectal swabs) at the time of presentation are necessary if antecedent C. jejuni is to be detected (114). Serologic studies may also be necessary as the median onset of neuropathic symptoms is 9 d after the onset of diarrhea (110).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Thus, stool analysis must be used systematically in cases of GBS, even if samples are taken late, and especially if there is prodromic diarrhea (20). Collection of two or three stool samples may also improve C. jejuni detection (11). As reported in previous studies (14,18,20), serology was by far the most sensitive technique, enabling two-thirds of C. jejuni-associated cases to be identified.…”
mentioning
confidence: 95%